1996
DOI: 10.1002/hrdq.3920070203
|View full text |Cite
|
Sign up to set email alerts
|

Learning self‐direction in a social and experiential context

Abstract: This article reviews eclectic research on how adults learn self-direction in a social and experiential context. The literature review synthesizes research from various social sciences with adult education. A cognitive-behaviorist model of learning, delineated in the article, suggests ways to help learners develop this orientation.By the year 2000, three-fourths of those entering the work force will have limited verbal and computational skills (Dole, 1989). The proportion of undereducated adults in the workplac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 7 publications
0
7
0
Order By: Relevance
“…This is not surprising in light of learning research arguing that multi-instructional training (based on multiple training methods) should be more beneficial (Merriam & Caffarella, 1999;Mezirow, 1985;Oddi, 1983;Piaget, 1966;Vann, 1996;Waddill & Marquardt, 2003). As an example, Juarez et al's (2006) study reported a training program that included panel presentations, home visits, book and video discussions, relationship-centered interview training, simulated patient sessions based on case analysis, and other methods.…”
Section: Training Instruction: Many Versus One Methodsmentioning
confidence: 97%
“…This is not surprising in light of learning research arguing that multi-instructional training (based on multiple training methods) should be more beneficial (Merriam & Caffarella, 1999;Mezirow, 1985;Oddi, 1983;Piaget, 1966;Vann, 1996;Waddill & Marquardt, 2003). As an example, Juarez et al's (2006) study reported a training program that included panel presentations, home visits, book and video discussions, relationship-centered interview training, simulated patient sessions based on case analysis, and other methods.…”
Section: Training Instruction: Many Versus One Methodsmentioning
confidence: 97%
“…Garrison (1997) addressed collaborative confirmation of personal meaning with others. Vann (1996) contended that self-direction in learning can be influenced by a process of human interaction, including the family, community, and workplace. This exploration ignites the expansion of the nature and realm of SDL to include interdependence, collaboration, and political aspect beyond just the autonomous and independent nature of SDL.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…As leaders, managers, and human resource professionals attempt to build learning infrastructures that leverage formal and informal learning, learners are being increasingly challenged to become continuous lifelong learners and assume more responsibility for their own learning and development so that they can remain employable and marketable (Carré, 2000;Dunlap & Grabinger, 2003;Durr, Guglielmino, & Guglielmino, 1996;London & Smither, 1999;Maurer, 2002;Stansfield, 1997;Vann, 1996). Concurrent with these chalThe author's intent is not to present a comprehensive review of literature on the topic of self-directed learning (SDL) but rather to offer an overview of key concepts and stimulate research interest on SDL within the context of HRD.The author would like to thank the issue editor,editors, and reviewers for their insightful and helpful comments on earlier versions of this article.This article was subjected to a two-tier blind review process that did not involve the author, who is currently a member of the ADHR Editorial Board.…”
mentioning
confidence: 99%